Viscoelastic bilinear cohesive model and parameter identification for failure analysis of adhesive composite joints. (15th September 2019) - Liu, P.F.; Peng, X.Q.; Guo, Z.Y.; Leng, J.X.; Jiao, L.
Abstract: Failure behaviors of adhesive composite joints under strain rate loading depend on time. This paper extends the rate-independent bilinear cohesive model to the viscoelastic case, where the regular instantaneous bilinear cohesive traction-separation function is kept and the additional rate-dependent traction is superimposed that is represented by the convolution between the rate of relaxation modulus and the regular instantaneous cohesive traction. The relaxation modulus is further expanded by the Prony series which are determined inversely by combining numerical and experimental results for single-lap adhesive joints under low strain rate loads. Explicit finite element analysis (FEA) is used to solve the instantaneous cohesive traction and to predict the rate-dependent failure behaviors of adhesive joints. Effects of some important factors including the cohesive strength and the load rate on the load responses are studied. Robust and mesh-independent numerical results are obtained by the developed viscoelastic cohesive model.